2014
DOI: 10.5511/plantbiotechnology.14.1112a
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein is formed from trienoic fatty acids in chloroplast: A targeted metabolomics approach

Abstract: Aldehydes and ketones produced from lipid peroxides (oxylipin carbonyls) exhibit a variety of biological activities ranging from the induction of defense genes to the irreversible damage to cells. Short oxylipin carbonyls such as acrolein and (E)-2-pentenal are responsible for tissue injury under environmental stress, but their production mechanism remains unclear. In this study, we elucidated the source fatty acids of short oxylipin carbonyls in leaves. We first established a comprehensive analysis of oxylipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 40 publications
(48 reference statements)
1
41
0
Order By: Relevance
“…Based on these reports, lipid-derived RCS diffused in plant cells might modify the gene expression network, which is not analyzed in this study, and cause the decrease of carbon utilization during the night and the growth retardation in aor mutants. Combining the results of Mano et al (2014a) and our study, we concluded that chloroplasts are a major production site of lipid-derived RCS and might be an initiator for lipidderived RCS-dependent signaling cascades in plant cells. Accordingly, further intensive studies are required to elucidate the molecular targets of lipidderived RCS, especially the receptors of lipid-derived RCS triggering the signal cascade in plant cells (Farmer and Mueller, 2013;Biswas and Mano, 2015).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Based on these reports, lipid-derived RCS diffused in plant cells might modify the gene expression network, which is not analyzed in this study, and cause the decrease of carbon utilization during the night and the growth retardation in aor mutants. Combining the results of Mano et al (2014a) and our study, we concluded that chloroplasts are a major production site of lipid-derived RCS and might be an initiator for lipidderived RCS-dependent signaling cascades in plant cells. Accordingly, further intensive studies are required to elucidate the molecular targets of lipidderived RCS, especially the receptors of lipid-derived RCS triggering the signal cascade in plant cells (Farmer and Mueller, 2013;Biswas and Mano, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…These facts suggest that chloroplasts are exposed to a high risk of lipid peroxidation. Indeed, Mano et al (2014a) reported that the Arabidopsis (Arabidopsis thaliana) fad7fad8 double mutant contained less lipidderived RCS (acrolein, crotonaldehyde, and malondialdehyde) in its leaves compared with wild-type leaves. Both Arabidopsis FAD7 and FAD8 encode chloroplastic v-3 fatty acid desaturases that convert 16:2 and 18:2 fatty acids into 16:3 and 18:3 fatty acids (Iba et al, 1993;McConn et al, 1994).…”
mentioning
confidence: 99%
“…oxylipin carbonyls; Farmer and Mueller, 2013). The chemical species of oxylipin carbonyl formed in the cells differ according to the fatty acids and the type of ROS involved (Grosch, 1987;Mano et al, 2014a).…”
mentioning
confidence: 99%
“…Formaldehyde, acetaldehyde, propionaldehyde, acrolein, malondialdehyde, (E)-2-hexenal, (Z)-3-hexenal, 4-hydroxy-(E)-2-hexenal and other carbonyls are found to be products of degradation of polyunsaturated fatty acids [450], and therefore aldehydes can be used as markers of lipid peroxidation. Measurement of coloured substances produced in a reaction between aldehydes and thiobarbituric acid (TBA) is the most commonly applied method [451].…”
Section: Reactions Of Roo • Ro • and Hydroperoxidesmentioning
confidence: 99%
“…Measurement of coloured substances produced in a reaction between aldehydes and thiobarbituric acid (TBA) is the most commonly applied method [451]. A new method for a comprehensive analysis of oxylipin carbonyls (quantitation and structural estimation) in plants with reverse-phase HPLC has recently been established [450,452]. …”
Section: Reactions Of Roo • Ro • and Hydroperoxidesmentioning
confidence: 99%